2018
DOI: 10.1016/s2542-5196(18)30001-9
|View full text |Cite|
|
Sign up to set email alerts
|

Ambient air pollution in relation to diabetes and glucose-homoeostasis markers in China: a cross-sectional study with findings from the 33 Communities Chinese Health Study

Abstract: The National Key Research and Development Program of China, the National Natural Science Foundation of China, the Fundamental Research Funds for the Central Universities, the Guangdong Province Natural Science Foundation, the Career Development Fellowship of Australian National Health and Medical Research Council, and the Early Career Fellowship of Australian National Health and Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(111 citation statements)
references
References 38 publications
7
103
1
Order By: Relevance
“…Individuals with T2DM have elevated cytokine levels in blood compared to people without diabetes and there is mounting evidence that supports that diabetes and particulate air pollution are associated with inflammatory dysregulation [22,93,94]. In addition, there is evidence that increased exposure to PM is significantly associated with increased fasting blood glucose (a biomarker for diabetes) in humans [73,95]. Whilst epidemiological evidence suggests that PM exposure is a risk factor for T2DM development, further research is required to better understand the cellular and molecular events underlying this as few studies have investigated the mechanism of toxicity, to date.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with T2DM have elevated cytokine levels in blood compared to people without diabetes and there is mounting evidence that supports that diabetes and particulate air pollution are associated with inflammatory dysregulation [22,93,94]. In addition, there is evidence that increased exposure to PM is significantly associated with increased fasting blood glucose (a biomarker for diabetes) in humans [73,95]. Whilst epidemiological evidence suggests that PM exposure is a risk factor for T2DM development, further research is required to better understand the cellular and molecular events underlying this as few studies have investigated the mechanism of toxicity, to date.…”
Section: Discussionmentioning
confidence: 99%
“…45 For the SO 2 , studies also showed similar mechanisms, such as inflammation 46 and dysfunction of pancreatic β-cells. 47 It has been argued that NO 2 and NO x can lead similar inflammation responses to those of particulate matter and O 3 . 48 The strengths of our study included the adjustment for multiple confounders including geographic, sex, BMI, smoking, alcohol consumption, socioeconomic status, and age variables that affected the individual studies, but were reduced by our study design.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution has become one of the most urgent health issues worldwide, causing 6.5 million premature deaths in 2015 11 . Additionally, air pollution has emerged as an unexpected risk factor for diabetes in many epidemiological 16 and rodent studies 12,13 . This association even occurs at air pollution levels well below those labelled as safe by the World Health Organization 14 .…”
Section: Figmentioning
confidence: 99%
“… Air pollution has emerged as an unexpected risk factor for diabetes 16 . The mechanisms linking air pollution and diabetes remain, however, unknown.…”
mentioning
confidence: 99%